Biophilic Design Approach in Yogyakarta Digital Art Design - Vianni Aninditia; Nurina Vidya Ayuningtyas (International Journal of Built Environment and Scientific Research, 2022)
The creative industry based on digital technology is the current strength of the creative industry in improving the national economy. In creating a national creative industry, every region in Indonesia is required to create space for creative industry players. The Digital Art Center is a building typology that can accommodate digital creative industry players to carry out all their activities. In the midst of the significant development of the creative industry, a healthy psychological and physical condition is needed to increase the creativity and productivity of industry players. Biophilic Design can help humans achieve prosperity and comfort, as well as increase creativity and productivity of creative industry players by shaping the built environment by creating human interaction with the surrounding natural elements. In addition, creating a space for interaction between humans can increase the sense of kinship and shape the user's psychology to be more positive. Thus, the design of the Yogyakarta Digital Art Center is expected to create human interaction with nature and human interaction that can increase the productivity and creativity of its users.